(NgANKELEWY I TEPLICEWY MATRICY I FORMY (B:s (NaLGEBRAI^ESKAQ TEORIQ (B/s - (NiOHWIDOW(B, (NiOSIF sEMENOWI^s ((NmOSKWA (B:s (NnAUKA(B,s, 1974)
(NsPISOK LIT(B.: (NS(B. 258 - 261 (57 (NNAZW(B.). (NpREDM(B. (NUKAZ(B.: (NS(B. 262 - 263s
Keywords: (NmATRICY (B((NMAT(B.)s; (NfORMY (B((NMAT(B.)s